The mediating role of knowledge-based capital for corporate entrepreneurship effects on performance: A study of small- to medium-sized firms - Simsek, Zeki; Heavey, Ciaran (Strategic entrepreneurship journal, 2011)
Even though research suggests that a firm's pursuit of corporate entrepreneurship directly contributes to its performance, we develop a deeper explanation, based on the insight that this pursuit develops and extends the firm's knowledge‐based capital. Specifically, we first demonstrate that the pursuit of corporate entrepreneurship enhances the firm's knowledge‐based capital residing in people (human capital), relationships (social capital), and systems (organizational capital). Then, we examine the mediating role of each capital type for corporate entrepreneurship effects on performance. We test our hypotheses using multisource data from a sample of CEOs and their top management teams in 125 firms, including a time‐lagged measurement of knowledge‐based capital and performance. Our findings provide general support for this theory and indicate that corporate entrepreneurship is positively associated with knowledge‐based capital and through this, with performance. Copyright © 2011 Strategic Management Society.